Engineering management and industrial engineering proceedings of the 2014 International Conference on Engineering Management and Industrial Engineering (EMIE 2014), Xiamen, China, 16-17 October 2014 - Leung, A. (CRC Press/Balkema, 2015)
Engineering Management and Industrial Engineering endeavors to provide a comprehensive and in-depth understanding of recent advances in management industrial engineering. The book is divided in the sections below:- Modeling, Simulation and Engineering Application- Manufacturing Systems and Industrial Design- Information Processing and Engineering- Innovation and Business Management- Engineering Education and Training- E-Business and E-Commerce- Tourism ManagementThe book will proof to be invaluable to professionals and academics in the above mentioned fields